Changes in the extent and structure of Norway spruce stands in the Ukrainian Carpathians based on forest survey data from 1988 to 2018 - Lavnyy Vasyl; Khomiuk Petro; Gusti Mykola; Havryliuk Serhii; Korol Mykola; Matusevych Oleksandr; Savchyn Volodymyr; Vonderach Christian; Kahle Hans-Peter (Central European Forestry Journal)
This study investigates dynamics of Norway spruce stands in the Ukrainian Carpathians in 1988–2018. Cultivation of Norway spruce has altered forest composition at the expense of site-adapted species. Climate change, with rising temperatures and altered precipitation has further impacted forest health and growth. Methods involve analyzing forest management databases from the Ukrainian State Forest Management Planning Association. Results indicate a decrease in Norway spruce stands area from 775.9 × 103 ha to 532.7 × 103 ha in 1988–2018, area-specific growing stock increased from 251 to 364 m3 ha−1. The share of mature and overmature stands increased from 35% to 52%, while for young and middle-aged stands the share decreased from 65% to 48%. The average potential wood production of fully stocked Norway spruce stands in the region is estimated to be about 9 m3 ha−1 year−1, while a considerable share of this potential may be lost due to mortality. For the survey periods 2011 and 2018 estimated gross periodic annual volume increment is larger than gross mean annual volume which is an indication that the analyzed stands in the average have not reached the age of biological rotation. The share of mixed Norway spruce – European beech forests increased from 10% to 25% of the total area. With ongoing climate change a further reduction in the share of Norway spruce is anticipated. However, actual potential for the use of Norway spruce wood in commercial Norway spruce forests is high. Conclusions highlight the need for adaptive forest management strategies to enhance the resilience and sustainability of site adapted Norway spruce stands amid environmental changes.